2006
DOI: 10.1098/rsta.2006.1767
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Cl homeostasis and volume regulation of the cardiac cell

Abstract: We aim at introducing a Cl- homeostasis to the cardiac ventricular cell model (Kyoto model), which includes the sarcomere shortening and the mitochondria oxidative phosphorylation. First, we examined mechanisms underlying the cell volume regulation in a simple model consisting of Na+/K+ pump, Na+-K+-2Cl- cotransporter 1 (NKCC1), cystic fibrosis transmembrane conductance regulator, volume-regulated Cl- channel and background Na+, K+ and Cl- currents. The high intracellular Cl- concentration of approximately 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…The ATP production rate was adjusted to obtain a steady state [ATP] of 7.0 mM, which was in the range of 5-10 mM [16] [17]. Second, the mechanisms of Cl -homeostasis and volume regulation [4,5] were incorporated by including ion flux via a Na + /K + /2Cl -cotransporter 1 (J NKCC1 ), background Cl -current (I Clb ), water flux, and LA. The magnitudes of I Clb and water flux were scaled according to the ratio of input capacitance between SANs and ventricular cells (Tables S4 and S9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ATP production rate was adjusted to obtain a steady state [ATP] of 7.0 mM, which was in the range of 5-10 mM [16] [17]. Second, the mechanisms of Cl -homeostasis and volume regulation [4,5] were incorporated by including ion flux via a Na + /K + /2Cl -cotransporter 1 (J NKCC1 ), background Cl -current (I Clb ), water flux, and LA. The magnitudes of I Clb and water flux were scaled according to the ratio of input capacitance between SANs and ventricular cells (Tables S4 and S9).…”
Section: Methodsmentioning
confidence: 99%
“…Using this model, we proposed the principal ionic mechanisms underlying the spontaneous action potential. In the current study, we revised the model by updating the ion channels and incorporating the mitochondria and β1-adrenergic cascade models described by Matsuoka et al (2004), Terashima et al (2006), Takeuchi et al (2006), and Kuzumoto et al (2007) [3][4][5][6] to analyze the roles of each target ion current, including the L-type Ca 2+ current (I CaL ), the sustained inward current (I st ), the hyperpolarizationactivated cation current (I ha ), and the slow component of the delayed rectifier K + current (I Ks ) in the positive chronotropy during β1-adrenergic stimulation. Our new model also includes an alteration of Ca 2+ dynamics during stimulation by calculating a modification of the Ca 2+ pump (SERCA) on the sarcoplasmic membrane.…”
mentioning
confidence: 99%
“…The overall ion traffic is described by a set of nonlinear and transcendental equations, which cannot be solved analytically. Numerical solutions of this problem have been developed in a series of studies [1,2,3,4,5,6,7,8,9,10]. Some of the published codes and executable files are available in a form that allows modification of kinetic parameters to some extent [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical solutions of this problem have been developed in a series of studies [1,2,3,4,5,6,7,8,9,10]. Some of the published codes and executable files are available in a form that allows modification of kinetic parameters to some extent [7,10]. Nevertheless, further study in this direction seems to be necessary because the reported detailed computations have been optimized only for certain cell types, such as human red blood cells and reticulocytes [3,10], guinea-pig cardiomyocytes [7], or frog skeletal muscle [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach is to provide the model implementation in an applicationspecific format, such as ICELL (Demir 2006), LABHEART (Puglisi & Bers 2001) or SIMBIO Terashima et al 2006). While this approach allows significantly greater scope for annotation of the model implementation, depending on the capabilities of the software, users of such model implementations are restricted to the original application environment.…”
Section: (B ) Physiome Standardsmentioning
confidence: 99%